Salmonella Gene rma (ramA) and Multiple-Drug-Resistant Salmonella enterica Serovar Typhimurium - van der Straaten, Tahar (American Society for Microbiology, 2004)
MarA and its homologue, RamA, have been implicated in multidrug resistance (MDR). RamA overexpression in Salmonella enterica serovar Typhimurium and Escherichia coli conferred MDR independently of marA. Inactivation of ramA did not affect the antibiotic susceptibilities of wild-type S. enterica serovar Typhimurium or 15 unrelated clinical MDR isolates. Thus, ramA overexpression is not a common MDR mechanism in Salmonella.